2013
DOI: 10.1212/wnl.0b013e3182a1ab12
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities on MRI in high-altitude U-2 pilots

Abstract: Pilots with occupational exposure to hypobaria showed a significant increase in WMH lesion volume and number. Unlike the healthy controls with predominantly WMH in the frontal white matter, WMH in pilots were more uniformly distributed throughout the brain. This is consistent with our hypothesized pattern of damage produced by interaction between microemboli and cerebral tissue, leading to thrombosis, coagulation, inflammation, and/or activation of innate immune response, although further studies will be neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 32 publications
(31 reference statements)
2
75
0
Order By: Relevance
“…Acute mountain sickness scores were higher, 34 and visual sensitivities were lower 35 in hypobaric than in normobaric hypoxia. Studies on U-2 pilots showed that hypobaria was associated with a change of white matter hyperintensity 14,36 and with the reduction of cortical thickness. 15 Moreover, exposure to hypobaria after traumatic brain injury worsened brain function.…”
Section: Effects Of Environmental Factors On Brain Structural Developmentioning
confidence: 99%
“…Acute mountain sickness scores were higher, 34 and visual sensitivities were lower 35 in hypobaric than in normobaric hypoxia. Studies on U-2 pilots showed that hypobaria was associated with a change of white matter hyperintensity 14,36 and with the reduction of cortical thickness. 15 Moreover, exposure to hypobaria after traumatic brain injury worsened brain function.…”
Section: Effects Of Environmental Factors On Brain Structural Developmentioning
confidence: 99%
“…6 Follow-up research reported significant elevation of WMH in high-altitude pilots without clinical symptoms of NDCS. 7 WMH are important markers of cerebral integrity in aging and brain disorders 8 linked to executive functioning, 9 processing speed, and general neurocognitive status, [9][10][11] and are an important predictor of increased neurocognitive decline.…”
mentioning
confidence: 99%
“…7 All DOCs were healthy at the time of study, without present or past history of any medical conditions associated with WMH or disqualifying for Flying Class II certification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Julian Hellmann-Regen, Kim Hinkelmann, Francesca Regen, Berlin, Germany: McGuire et al 1 presented interesting data on the prevalence and location of white matter hyperintensities (WMHs) in MRI scans of highaltitude pilots. The authors demonstrated that WMHs differ between the pilot group and a matched group of healthy controls.…”
Section: White Matter Hyperintensities On Mri In High-altitude U-2 Pimentioning
confidence: 99%